Ribosomal DNA evolution and gene conversion in Nicotiana rustica - Matyasek, R; Lim, K Y; Kovarik, A; Leitch, A R (Heredity, 2003)
Genomic in situ hybridisation was used to confirm that Nicotiana rustica (2n=4x=48) is an allotetraploid between N. paniculata (2n=2x=24, maternal P-genome donor) and N. undulata (2n=2x=24, paternal U-genome donor), their progenitors or species closely related to them. Fluorescent in situ hybridisation showed that N. paniculata has one 5S and two 18-5.8-26S rDNA loci whereas N. undulata has an additional 18-5.8-26S rDNA locus. N. rustica has the sum of the loci found in these putative parents. The sizes of the 18-5.8-26S rDNA loci indicate that the number of rDNA units on the U-genome chromosomes has amplified; perhaps this is associated with a concomitant reduction in the number of units on P-genome chromosomes. Restriction fragment length polymorphism analysis of the intergenic spacer (IGS) of the 18-5.8-26S rDNA units in N. rustica and the two progenitor diploids revealed that about 80% of IGS sequences in N. rustica are of an N. undulata type and 20% of N. paniculata type. These data indicate that interlocus sequence homogenisation has caused the replacement of many N. paniculata-type IGSs in N. rustica with an N. undulata-type of sequence. It is probable that subsequent to this replacement there has been sequence divergence at the 5' end of the IGS. As in tobacco, an allotetraploid between N. sylvestris and N. tomentosiformis, the direction of the IGS interlocus conversion is towards the paternal genome donor.
Keywords: Multigene Family; genová konverze; Genome, Plant; genom rostlinný; hybridizace in situ fluorescenční; intergenová DNA; ribozomální DNA; molekulární evoluce; Evolution, Molecular; Gene Conversion; mezerníky ribozomální DNA; DNA rostlinná; DNA, Plant; Nicotiana; DNA, Intergenic; In Situ Hybridization, Fluorescence; DNA, Ribosomal Spacer; Polyploidy; DNA, Ribosomal; multigenová rodina; tabák; polyploidie